MEDICAL STUDENTS’ PERCEPTIONS OF VIRTUAL LEARNING DURING THE COVID-19 PANDEMIC - Yemima. Pakiding; Jason Sriwijaya (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Coronavirus Disease (COVID-19) Pandemic has affected almost every aspect of our life. The virus spreads rapidly via droplets and airborne particles. Thus, keeping a distance is crucial. The university transforms the conventional methods of teaching and learning into virtual learning, a system that utilizes technology and internet connection to prevent the spread of COVID-19. This sudden change certainly affects students’ comprehensive, psychological, and learning aspects. As a result, not only from financial burden for internet costs and devices used but also causing physical and mental consequences. The study aimed to see the impact of students' perceptions of virtual learning during the COVID- 19 pandemic.Methods: Using a descriptive observational design with qualitative and quantitative data. The sample was obtained from Medical Students of Hasanuddin University (MSHU) who met the inclusion criteria using probability sampling-stratified random sampling.Results: Descriptive analysis shows that 56,5% of students negatively perceive virtual learning. However, 58.9% still agree with implementing online lectures during the pandemic. Moreover, 71.4% of students experienced learning style changes, 62.5% assumed virtual learning would affect their grades, and 78.6% suggested hybrid learning methods for their future preferences.Conclusion: In general, MSHU has a negative perception of virtual learning but agrees with its implementation during the pandemic. The results also recommend a future learning method: a Hybrid method, a combination of in-person and virtual learning.